The used of chopped banana Musa paradisiaca stem for stimulating immune responses and streptococcosis resistance of Nile tilapia Oreochromis niloticus - Lilis Nurjanah; Sri Nuryati; Alimuddin Alimuddin; Kukuh Nirmala (Jurnal Akuakultur Indonesia)
ABSTRACT